The Relationship Nurses' Knowledge and Implementation of Early Warning Score (EWS) In Critical Patients at Sulianti Saroso Infectious Disease Hospital - Nuning Handayani; Achmad Fauzi; Romaida Romaida; Farida Murtiani (STIKep PPNI Jawa Barat, 2022)
Aims : To find out the relationship between nurses' knowledge of EWS and the implementation of EWS in critically ill patients. Design : Quantitative research with cross sectional design Methdos : The sample was taken using a total sampling technique of 109 nurses at Sulianti Saroso Infectious Disease Hospital for the period of December 2021. Data collection used questionnaires and observation. Univariate analysis using frequency distribution, bivariate analysis using chi-square analysis. Results : The results showed that of the 109 nurses, most of the knowledge about EWS had good knowledge about the Early Warning Score (EWS), namely 61 respondents (56%). Most of the EWS implementations are Early Warning Score (EWS) implementations in the appropriate category, namely 69 respondents (63.3%). There is a relationship between knowledge and the implementation of EWS in critical patients P value = 0.000. Conclusions : The study recommends the need for policies and standard operating procedures (SOPs) for EWS and it is necessary to carry out socialization and training on EWS SOPs to all health workers on a regular basis accompanied by regular evaluations.